Cell division symmetry control and cancer stem cells - Majumdar, Sreemita (AIMS Mol Sci, 2020)
Stem cells including cancer stem cells (CSC) divide symmetrically or asymmetrically. Usually symmetric cell division makes two daughter cells of the same fate, either as stem cells or more differentiated progenies; while asymmetric cell division (ACD) produces daughter cells of different fates. In this review, we first provide an overview of ACD, and then discuss more molecular details of ACD using the well-characterized Drosophila neuroblast system as an example. Aiming to explore the connections between cell heterogeneity in cancers and the critical need of ACD for self-renewal and generating cell diversity, we then examine how cell division symmetry control impacts common features associated with CSCs, including niche competition, cancer dormancy, drug resistance, epithelial-mesenchymal transition (EMT) and its reverse process mesenchymal-epithelial transition (MET), and cancer stem cell plasticity. As CSC may underlie resistance to therapy and cancer metastasis, understanding how cell division mode is selected and executed in these cells will provide possible strategies to target CSC.